PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA HOTEL ASEAN PEKANBARU - Harwina, Yulia (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted in Pekanbaru Asean Hotel located at Jl. Sudirman Pekanbaru. The research objective is to determine and analyze the effect of job satisfaction and organizational culture simultaneously influence the performance of employees at Asean Hotel Pekanbaru. To know and analyze job satisfaction and organizational culture partial effect on the performance of employees at the Hotel Asean Pekanbaru and to identify and analyze which variables are the dominant influence on the performance of employees at Asean Hotel Pekanbaru. To achieve these objectives the research conducted by using the sample of 75 people, using Census. Data analysis method using simultaneous test and partial test (multiple linear regression analysis with SPSS Windows version 20). Results of this study resulted in the simultaneous known that job satisfaction and organizational culture influence on the performance of employees at Hotel Asean. Partially known that job satisfaction and organizational culture influence on the performance of employees at Asean Hotel Pekanbaru. The result showed that the most dominant factor affecting the performance of employees at Asean Hotel Pekanbaru is the factor of quality of service. Recommendations can be the authors propose is Asean Hotel Pekanbaru should pay attention to employee satisfaction which is part of the demands of life, the sense of satisfaction to the task or job, satisfied with the boss and satisfied with co-workers will affect the feelings of employees and will further affect the implementation of the activity.Â